2018
DOI: 10.1214/17-ps285
|View full text |Cite
|
Sign up to set email alerts
|

On the scaling limits of weakly asymmetric bridges

Abstract: We consider a discrete bridge from (0, 0) to (2N, 0) evolving according to the corner growth dynamics, where the jump rates are subject to an upward asymmetry of order N −α with α ∈ (0, ∞). We provide a classification of the asymptotic behaviours -invariant measure, hydrodynamic limit and fluctuations -of this model according to the value of the parameter α.MSC 2010 subject classifications: Primary 60K35; secondary 60H15; 82C24.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Besides the work of [BG97,ACQ11] (and previous to the present work), the only other result of this type via Gärtner / Cole-Hopf transform is due to [DT16], wherein they show KPZ equation convergence for a class of weakly asymmetric non-simple exclusion processes with hopping range at most 3. Another work which was posted slightly after our present article is by Labbé [Lab16b,Lab16a] who showed that in particular INTRODUCTION range of scaling regimes the fluctuations of the weakly asymmetric bridges converge to the KPZ equation, also via the method of Gärtner transform.…”
Section: Introductionmentioning
confidence: 85%
“…Besides the work of [BG97,ACQ11] (and previous to the present work), the only other result of this type via Gärtner / Cole-Hopf transform is due to [DT16], wherein they show KPZ equation convergence for a class of weakly asymmetric non-simple exclusion processes with hopping range at most 3. Another work which was posted slightly after our present article is by Labbé [Lab16b,Lab16a] who showed that in particular INTRODUCTION range of scaling regimes the fluctuations of the weakly asymmetric bridges converge to the KPZ equation, also via the method of Gärtner transform.…”
Section: Introductionmentioning
confidence: 85%
“…An important feature of this hyperbolic PDE is that, for any initial condition, it reaches the macroscopic stationary state x → x ∧ (1 − x) in finite time. Notice that for α ≥ 1, the hydrodynamic limit is given by a heat equation so that it takes infinite time to reach the stationarity state, see [Lab16]. This feature of the PDE has a non-trivial consequence at the level of the KPZ fluctuations, that we now investigate.…”
Section: Hydrodynamic Limitmentioning
confidence: 91%
“…Theorem 1.1 ( [Lab16]) Take α ∈ (0, 1). The law of the process u N under µ N converges to the law of the centred Gaussian process (B α (x), x ∈ R), with covariance…”
Section: Invariant Measure and Equilibrium Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations